2003
DOI: 10.1074/jbc.m212301200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Expression of the ROMK (Kir 1.1) Channel Is Regulated by the Aldosterone-induced Kinase, SGK-1, and Protein Kinase A

Abstract: The Kir1.1 (ROMK) subtypes of inward rectifier K ؉ channels mediate potassium secretion and regulate sodium chloride reabsorption in the kidney. The density of ROMK channels on the cortical collecting duct apical membrane is exquisitely regulated in concert with physiological demands. Although protein kinase A-dependent phosphorylation of one of the three phospho-acceptors in Kir1.1, Ser-44, also a canonical serum-glucocorticoid-regulated kinase (SGK-1) phosphorylation site, controls the number of active chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 54 publications
6
146
0
4
Order By: Relevance
“…In the CCD (27) and the CNT (28), ROMK is up-regulated in the apical membrane by a high K diet. Aldosterone increases ROMK in the apical membrane of the rat CCD (29). Consistent with the present results, a high K diet induced charybdotoxin-sensitive K secretion in the late distal tubule of the mouse as assessed by micropuncture (30).…”
Section: Discussionsupporting
confidence: 78%
“…In the CCD (27) and the CNT (28), ROMK is up-regulated in the apical membrane by a high K diet. Aldosterone increases ROMK in the apical membrane of the rat CCD (29). Consistent with the present results, a high K diet induced charybdotoxin-sensitive K secretion in the late distal tubule of the mouse as assessed by micropuncture (30).…”
Section: Discussionsupporting
confidence: 78%
“…We and others have observed that only a small fraction of ROMK1 is actually expressed in the plasma membrane of COS7 cells transfected with ROMK1 (23,24). Fig.…”
Section: Inhibition Of Ubiquitination Increases the Surface Expressiomentioning
confidence: 99%
“…34 It has also been suggested that sgk1 may regulate ENaC subunit gene expression. 35 Sgk1 has also been reported to phosphorylate the Kir1.1 (ROMK) subtype of inward rectifier K ϩ channel, thereby increasing channel density; 36 such an effect may contribute to the kaliuretic action of aldosterone. The mild aldosterone-resistant phenotype of the sgk1 null mice is in contrast to that of MR or ENaC-subunit null mice; 29,37 this may indicate that sgk1 is not the exclusive effector of aldosterone action or that other isoforms of sgk, sgk2, and sgk3, although not normally regulated by corticosteroids, may be able to compensate in this model.…”
Section: Epithelial Aldosterone-induced Proteinsmentioning
confidence: 99%